Black Buck - Askaripour, Mateo (Houghton Mifflin Harcourt, 2021)
"Darren lives in a Bed-Stuy brownstone with his mother, content working at Starbucks in the lobby of a Midtown office building, hanging out with his girlfriend, Soraya, and eating his mother's home-cooked meals. A chance encounter with Rhett Daniels, CEO of Sumwun, NYC's hottest tech startup, results in an exclusive invitation for Darren to join an elite sales team on the thirty-sixth floor. As the only Black person in the company, Darren reimagines himself as "Buck," a ruthless salesman unrecognizable to his friends and family. When things turn tragic at home, Buck begins to hatch a plan to help young people of color infiltrate America's sales force, setting off a chain of events that changes the game."--Publisher.